The Balvarran Cupped Stone, the ’Bloody Stone’ of Dunfallandy, and a Cup-marked Stone in Glen Brerachan - Dixon, John H (Proceedings of the Society of Antiquaries of Scotland, 1921)
An account of three cup-marked stone outcrops and the local legends traditionally attached to them.